Long‐Life Pillar[5]quinone Cathode for Aqueous Zinc‐Ion Batteries - Prof. Serkan Yeşilot; Yasemin Solmaz; Dr. Nazmiye Kılıç; Burcu Unal; Prof. Ozlem Sel; Prof. Rezan Demir‐Cakan (ChemElectroChem)
Abstract Aqueous zinc ion batteries (ZIBs) are currently gaining a significant amount of attention as a low‐cost and high safety energy storage option. While mostly inorganic structures are used as cathode materials in aqueous zinc batteries, these materials undergo structural degradation, therefore, alternative organic cathodes are expected to be developed to replace inorganic materials in aqueous zinc ion batteries (AZIBs). In this work, pillar[5]quinone (P5Q) is used as a cathode in AZIBs for the first time. Besides investigating the charge storage mechanism and interfacial property evolution of P5Q by various ex situ analyses, electrochemical quartz crystal microbalance (EQCM) and density functional theory (DFT) demonstrates both Zn2+ and H+ incorporation. The P5Q exhibits >99 % Coulombic efficiency through 10000 cycles at ultra‐fast (500 C) current density, yielding a capacity value of approximately 120 mAh g−1 at the end of the cycle. When the current density is changed from 500 C to 120 C, an initial discharge capacity of approximately 182 mAh g−1 is achieved, demonstrating outstanding performance with over 80 % capacity retention for the subsequent 7000 cycles.